2022
DOI: 10.1186/s12909-022-03608-z
|View full text |Cite
|
Sign up to set email alerts
|

Can interprofessional education change students’ attitudes? A case study from Lebanon

Abstract: Background Interprofessional collaboration is key to improving the health of individuals and communities. It is supported by provision of Interprofessional education (IPE) which has recently emerged in the Middle East region. This study investigated changes in healthcare students’ attitudes towards interprofessional collaboration after undertaking the Interprofessional Education and Collaboration (IPEC) course. Methods A paper-based anonymous surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
1
0
4
Order By: Relevance
“…The IPAS is a valid and reliable instrument to measure attitudes about interprofessional learning and is used in different settings and to measure changes through IPE interventions [25][26][27][28][29][30][31][32][33][34]. When comparing the pre-and post-training results of both groups in our study, we found a significant improvement in the subscale "teamwork, roles and responsibilities" and in the self-developed interprofessional error communication scale.…”
Section: Discussionmentioning
confidence: 56%
“…The IPAS is a valid and reliable instrument to measure attitudes about interprofessional learning and is used in different settings and to measure changes through IPE interventions [25][26][27][28][29][30][31][32][33][34]. When comparing the pre-and post-training results of both groups in our study, we found a significant improvement in the subscale "teamwork, roles and responsibilities" and in the self-developed interprofessional error communication scale.…”
Section: Discussionmentioning
confidence: 56%
“…33 Problem-based learning (PBL) diterapkan pada penelitian oleh tiga artikel. 26,29,34 Metode PBL menitikberatkan pembelajaran diskusi klinis untuk mengapresiasi perspektif dari disiplin yang berbeda dan bagaimana aspek tersebut diintegrasikan dengan pengetahuan sebelumnya. 29 Pembelajaran action based lainnya yaitu Team-based learning (TBL) yang diterapkan pada salah satu artikel dalam format workshop tatap muka berbasis kasus dengan diskusi dan tanya jawab.…”
Section: Metode Pembelajaranunclassified
“…46 Kompetensi komunikasi interprofesional hanya ditemukan pada satu artikel yang secara spesifik Terdapat satu penelitian yang tidak menemukan peningkatan yang signifikan setelah dijalankannya program IPE. 34 Hasil skor post-test menunjukkan penurunan tidak signifikan pada domain sikap terhadap patient centeredness. Hasil ini sejalan dengan penelitian yang mengimplementasikan IPE dengan metode case-based workshop dan penggunaan instrumen Interprofessional Attitude Scale (IPAS) pada mahasiswa farmasi.…”
Section: Capaian Kompetensi Inti Inteprofessional Collaborative Pract...unclassified
See 2 more Smart Citations